A Longitudinal Study of Illinois State Scholarship Commission Monetary Award Recipients, 1967-1974 - Boyd, Joseph D.; Fenske, Robert H.; Illinois State Scholarship Commission, Deerfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The present effectiveness and future direction of monetary award programs administered by the Illinois State Scholarship Commission is examined in three surveys. A random sample of 1,000 was drawn from the total number of scholarship recipients during the 1967-68 and 1970-71 academic years; 2,000 from the 1973-74 survey. It is shown that: (1) scholarship respondents were divided about evenly between men and women, with slightly more men in the grant respondent groups; (2) the grant group includes substantially more commuters (54 percent) than the scholarship group, which is related to the greater percentage of grant respondents enrolled in public two-year colleges; (3) both scholarship and grant group distributions are skewed toward the freshman and sophomore levels; and (4) decreasing percentages of grant respondents attend private four-year colleges over the period studied, with a shift from private four-year colleges to public two-year colleges. The distribution is more stable for scholarship respondents. These findings are discussed in terms of the impact of awards on access and choice of college, theory and reality of financing a college education, opinions and attitudes toward financial aid. The findins can also be applied to operational decisions regarding student financial aid administration and policies. (LBH)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Educational Finance; Enrollment; Financial Policy; Higher Education; Longitudinal Studies; Public Education; Scholarships; School Surveys; Sex (Characteristics); State Aid; Student Distribution; Student Loan Programs; Tuition Grants; Illinois; Reports, Descriptive